TAX AND ECONOMIC GROWTH IN NIGERIA: AN ARDL APPROACH - Nwanakwere, Justine Tochukwu (Jurnal Ekonomi & Studi Pembangunan, 2019)
This study investigates the relationship between tax and economic growth (GDP) using the Auto-Regressive Distributed Lag (ARDL) bound test approach. The study further decomposed tax into company income tax (CIT), petroleum profit tax (PPT), value-added tax (VAT) and excise and custom duties (ECD), then examined the effect of each of them on economic growth. The data for the study were obtained from Federal Inland Revenue Service (FIRS) and Central Bank of Nigeria (CBN) bulletin, spanning from 1981-2014. The ARDL results show no cointegration among the variables. Interestingly, the short run results reveal that total tax is insignificant while the decomposed taxes are significant. Petroleum profit tax and value-added tax have positive relationship with GDP while company income tax and excise and custom duties have negative relationship with GDP. From these findings, the study recommends an effective use of taxation so as to improve the impact of tax on the Nigerian economy. Also, efficient tax regulation should be put in place to mitigate the issue of tax evasion, especially among firms and corporate entities, and improve the contribution of CIT to economic growth.